Developing English Listening Learning Model Infused with Project-Based Learning and Digital Scholarship for Autonomous Learners - Mardiana, Rizdika; Sumarni, Sri; Dewanti, Ratna; Iskandar, Ifan; Sulistyaningrum, Siti Drivoka; Ramadhanty, Fadhilah (English Teaching and Linguistics Journal (ETLiJ), 2024)
This study aims to develop an English listening learning model infused with project-based learning and digital scholarship for autonomous learners. Digital scholarship (DS) is one element of eco-literacy that uses digital tools and technologies to make teaching and learning easier. Project-based learning (PjBL) is much better at offering contextualized, hands-on learning experiences that encourage critical thinking in the face of challenging problems. The descriptors of autonomous learners are infused into the existing learning model to create a dynamic and enriching educational experience for autonomous 10th-grade students. Conducted at a senior high school in Bogor, West Java province, the four steps of modified design and development research—need analysis, design, development, and evaluation—were applied in this study. The data were gathered by observation, interviewing, and syllabus analysis of the existing learning paradigm and reviewing pertinent research on PjBL, DS, autonomous learning, and listening comprehension. After a review of the relevant literature, it was discovered that three of eleven PjBL descriptors, five of the twenty-five DS descriptors, six of eleven B1 listening skill descriptors, and two of eleven autonomous learner descriptors had been included in the current learning model. A conceptual framework is used to develop the existing learning model to be an English listening learning model infused with project-based learning and digital scholarship for autonomous learners.